Remote sensing data for calibrating hydrologic modeling: Hydrological impacts of land use change of the Reventado river sub-basin, Costa Rica - Tapia-Arenas, Claudia Andrea (2020)
The “Ecological rehabilitation pilot plan of the Irazú Volcano National Park – Prusia Sector” intends to determine an ecological rehabilitation plan for current 54-year unmanaged exotic forest plantation. This study aims to determine water balance impacts on land cover changes over the Reventado river sub-basin. Thus, three scenarios were considered: Current (current cover conditions), Pasture (exotic forest plantations converted to pasture) and Forest (exotic forest plantations to natural forest). No field data was available for calibration; therefore MODIS16A2 product was used to calibrate evapotranspiration from hydrologic modeling using SWAT. An analysis was performed to determine if estimates vary using two models: 1) parameterized but non-calibrated approach(PNCA), and 2) parameterized and calibrated approach (PCA). Overall, using MODIS16A2 for calibration was satisfactory, showing statistically significant differences in ET, PERC, SURQ and GWQ. The PCA was then used for estimating the impact on water balance variables due to land cover change scenarios –previously mentioned. Slightly differences between Current and Forest scenarios were perceived, whereas Pasture showed 5 % annual increment in surface runoff and 3 % annual decrement of ground water contribution to stream. Thus, careful wood extraction and rehabilitation planning is needed in order to assure low impacts in the hydrological behavior of the sub-basin.